Effects of Quercetin and Omega-3 Combination on Nuclear Factor Kappa B (NFκB) Expression Level in Pancreatic Tissue of Rats with Type-2 Diabetes Mellitus - Asri Hendrawat,; Mujiyanto Winardi, (Journal of Pharmacy and Nutrition Sciences, 2017)
Background: Hyperglycemia increases nuclear factor kappa B (NFκB) expression and promotes cellular injury. Quercetin and omega-3 are expected to regulate NFκB expression. This study aims to measure the effect of combination therapy with quercetin and omega-3 in lowering the expression of NFκB in the pancreatic tissue of rats with type-2 DM as compared to those treated with monotherapy with either agent. Methods: This experimental study involved the use of a paraffin block of pancreatic tissue from 24 male Wistar rats aged 3 months, weighing between 250 g and 350 g. All rats underwent induction of type-2 DM and were divided into 4 groups: K1 (treated daily with placebo), K2 (treated with quercetin at 20 mg·kgBW-1·d-1), K3 (treated with omega-3 at 100 mg·kgBW-1·d-1), and K4 (treated with quercetin at 20 mg·kgBW-1·d-1 and omega-3 at 100 mg·kgBW-1·d-1). Treatments were administered orally for four weeks. Once the treatment was completed, samples of pancreatic tissue were collected for the measurement of the percentage of NFκB expression using immunohistochemical (IHC) staining. Results:The average level of NFκB expression in the pancreatic nuclei of DM rats treated with the combination of omega-3 and quercetin was significantly lower than that of those treated with placebo, quercetin only, or omega-3 only (p < 0.05). Conclusion: The combination of quercetin at 20 mg·kgBW-1·d-1 and omega-3 at 100 mg·kgBW-1·d-1 is significantly more effective in lowering the percentage of NFκB in pancreatic nuclei than monotherapy with either agent.